Creative drama in English class: Boosting student self-esteem through innovation - Syahal Waludin; Sri Setyarini (Inovasi Kurikulum, 2025)
In Indonesia, the integration of creative drama into the formal curriculum has not been widely or systematically implemented, leaving substantial room for the development of students' emotional aspects, especially self-esteem, as an area of potential that has not been utilized. The purpose of this study is to examine how the addition of creative drama to the school curriculum can improve students' self-esteem in secondary schools. This study employs a qualitative approach using a participatory case study method at SMP PGRI Lembang, with primary informants including seventh and eighth-grade students, the school principal, and two teachers. Data was collected through observation, in-depth interviews with one school principal and two teachers, and documentation of learning activities. Thematic coding-based content analysis was used to analyze the data. The findings indicate that the use of structured creative drama significantly improves students' self-confidence, social courage, and self-expression. Activities such as improvisation, role-playing, and group reflection serve as effective means to develop students' affective dimensions, particularly self-esteem. This study concludes that the integration of creative drama and Project-Based Learning (PjBL) principles facilitates collaborative, reflective, and transformative learning experiences and can serve as an innovative learning model aligned with the ideals of the Kurikulum Merdeka.   Abstrak Di Indonesia, integrasi drama kreatif ke dalam kurikulum formal belum diterapkan secara luas atau sistematis, sehingga menyisakan ruang substansial untuk pengembangan aspek emosional peserta didik terutama harga diri sebagai area potensi yang belum dimanfaatkan. Tujuan penelitian ini untuk mengkaji bagaimana penambahan drama kreatif dalam kurikulum sekolah dapat meningkatkan harga diri peserta didik di sekolah menengah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus partisipatif di SMP PGRI Lembang, dengan informan utama berupa peserta didik kelas tujuh dan delapan, kepala sekolah, dan dua guru. Data dikumpulkan melalui observasi, wawancara mendalam dengan satu kepala sekolah dan dua guru, serta dokumentasi aktivitas belajar. Analisis isi berbasis pengkodean tematik digunakan untuk menganalis data. Temuan menunjukkan bahwa penggunaan drama kreatif yang terstruktur secara signifikan meningkatkan kepercayaan diri, keberanian sosial, dan ekspresi diri peserta didik. Aktivitas seperti improvisasi, peran-peran, dan refleksi kelompok menjadi sarana efektif untuk mengembangkan dimensi afektif peserta didik, terutama harga diri. Studi ini menyimpulkan bahwa integrasi drama kreatif dan prinsip-prinsip Pembelajaran Berbasis Proyek (PjBL) memfasilitasi pengalaman belajar kolaboratif, reflektif, dan transformatif, serta dapat menjadi model pembelajaran inovatif yang selaras dengan idealisme Kurikulum Merdeka. Keywords: drama kreatif; pembelajaran berbasis proyek; pendidikan afektif; penghargaan diri.